India steps ahead to curb anemia: Anemia Mukt Bharat - Bhatia, Vikas; Sahoo, Durgesh Prasad; Parida, Swayam Pragyan (Indian Journal of Community Health, 2018)
Anemia is a major public health problem in India affecting over half of population in almost all age groups. It has devastating effect on human health and affects the socio-economic development. Government has devised several programs like National Nutritional Anemia Control Program (NNACP), Weekly Iron and Folic Acid Supplementation (WIFS), National Iron Plus Initiative (NIPI) etc to combat anemia. The facts remain that in spite of all the programs, no marked improvement has been noticed in the magnitude of anemia. A holistic approach is required with special emphasis on community awareness about consequences of anaemia and benefits of Iron Folic Acid (IFA) supplementation, uninterrupted supply availability of Iron folic Acid tablets and syrups, hard to reach areas and monitoring and review system to find out adequacy in terms of participation and frequency of meetings and problem-solving in NIPI